Відображення національної картини світу в семантиці фразеологізмів - Орел, Ірина Іванівна; Orel, I. I. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У розвідці зроблено спробу описати вплив менталітету народу на формування національної картини світу та відображення її у фразеологічній семантиці. Фразеологізми розглянуто як мовні знаки й знаки культури, що репрезентують національну культуру в мові. Описано способи формування, збереження та передачі національно-культурної інформації, розглянуто менталітет як систему національно-специфічних образів, виявлено відобра¬ження вказаних образів у фразеологічній семантиці, виокремлено фрагменти національної картини світу, які сприяють фіксації національно-специфічних образів та передачі національно-культурної інформації у семантиці фразеологізмів. The influence of people’s mentality on world national picture and its reflection in the phraseological semantics are described in the research. The aim of the article is to identify and to describe ways of world national picture reflection in language semantics. The ways of forming, storing and transforming mentality are studied to reach the aim; mentality as a system of nationally specific images is considered; the attempt to describe ways of specified images reflection in phraseology semantics is made; world national picture fragments which contribute to nationally specific images fixation in phraseology significance are isolated. Performance of given tasks allows to reveal mechanism of national cultural information storing in semantics, to trace ways of extralinguistic reflection of reality in phraseology. Several fragments of world national picture which served as an impulse for analyzed language units forming are isolated by us. The given facts point to nationally specific division of the world, they demonstrate national cultural peculiarities of world language picture, they confirm necessity of national and cultural character background knowledge mastering for adequate understanding of phraseology significance.
Reflection of the World National Picture in Phraseological Semantics
Keywords: фразеологічна одиниця; phraseological units; менталітет; mentality; національна картина світу; worlds national picture